MODEL PEMBELAJARAN PAIR CHECKS DAN HASIL BELAJAR BAHASA JERMAN SISWA SMA NEGERI 1 AMBON - Laurisye S Salamony; Samuel Jusuf Litualy; Grietje H Kunu (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2021)
This study aims to determine the effect of using the pair checks learning model on student learning outcomes in German at SMA Negeri 1 Ambon. The sample consisted of 37 students from the 'Cross -Interests XI MIA 1 and XI MIA 2' classes. This study has two variables, namely the learning mode "Pair Checks" as the independent variable and German learning outcomes as the dependent variable. The research data were obtained through the tests, the first test was a pre-test (before using the "Pair Checks" learning model in class) and then the data were processed using the "Dependent T-Test" technique. The calculation results show that t calculates: 14.09, level Î± = 5% higher than t table = 1, 68. Thus, the calculation results show that there is a significant effect of using the Pair Checks learning model on German learning outcomes. Therefore, it is recommended to apply the Pair Checks learning model in the classroom to improve German learning outcomes